Effects on permanent teeth after luxation injuries to the primary predecessors: a study in children assisted at an emergency service - Da Silva Assuncao, Luciana Reichert; Ferelle, Antonio; Hiromi Iwakura, Maria Luiza; Cunha, Robson Frederico [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Aim: The purpose of this study is to evaluate the developmental disturbances in permanent teeth as a result of luxation injuries in the primary teeth predecessors. Material and methods: A total of 5330 records, corresponding to 10 years attendance at the Emergency Center of Baby Clinic, Londrina State University, Brazil, were analyzed. Three hundred and eighty nine children were involved in this study, totaling 620 traumatized primary teeth. Clinical and radiographic examinations were carried out in the permanent successor teeth. Results: In total, 623 permanent teeth were examined and developmental disturbances were detected in 126 teeth (20.2%). The white or yellow-brown discoloration of enamel was the clinical disturbance most observed (78.0%) and the crown alteration most detected through radiographic analysis was hypoplasia (86.0%). Root alterations were rare; root dilaceration was observed in only one case. The age of the children when their primary teeth received damage varied between 6 and 36 months (P = 0.000325). Intrusive luxation and avulsion were related with most of the cases of sequelae in the successor permanent teeth (P = 0.000001). Conclusion: The results of the present investigation emphasize the special attention required for children who suffered dental trauma at an early age, especially in cases of intrusive luxation and avulsion.